QUESTIONS OF INFORMATIONAL SECURITY OF KHERSON STATE UNIVERSITY - Mazur, A.B.; Svetlanov, І.Л. (Journal of Information Technologies in Education (ITE), 2009)
The article deals with problems of informational security of modern organizations and analyzes relevant questions of computer security at Kherson State University.